Implementasi Media Visualisasi 360 Pada Platform Android Untuk Promosi Penjualan Kendaraan Bekas - Abdul Rokhim; Sri Ayu Lestari (Universitas Islam Lamongan, 2019)
Media to promote and market an item is very important, good promotion can support the sale of goods marketed. Marketing media even now has begun to vary as advertisements on mass media, internet, brochures and other print media. Website is a media that is currently widely used in introducing products or services. Dillah Motor Tambakrejo is a dealer that sells used motorbikes and cars. utilizing Android as a smartphone communication tool has experienced development at this time, such as media tools to promote vehicles using 360 media visualization tours. Where applications can visualize used motorbikes and cars using 360 virtual media that can be seen 360 degrees of vision and consumers can know the details / parts of the motor and specifications of this motorbike